Minds and Brains, Sleep and Psychiatry. Issue 1 (10th November 2020) - Hobson, J. Allan; Gott, Jarrod A.; Friston, Karl J.
Abstract : Objective: This article offers a philosophical thesis for psychiatric disorders that rests upon some simple truths about the mind and brain. Specifically, it asks whether the dual aspect monism —that emerges from sleep research and theoretical neurobiology—can be applied to pathophysiology and psychopathology in psychiatry. Methods: Our starting point is that the mind and brain are emergent aspects of the same (neuronal) dynamics; namely, the brain–mind. Our endpoint is that synaptic dysconnection syndromes inherit the same dual aspect; namely, aberrant inference or belief updating on the one hand, and a failure of neuromodulatory synaptic gain control on the other. We start with some basic considerations from sleep research that integrate the phenomenology of dreaming with the neurophysiology of sleep. Results: We then leverage this treatment by treating the brain as an organ of inference. Our particular focus is on the role of precision (i.e., the representation of uncertainty) in belief updating and the accompanying synaptic mechanisms. Conclusions: Finally, we suggest a dual aspect approach—based upon belief updating (i.e., mind processes) and its neurophysiological implementation (i.e., brain processes)—has a wide explanatory compass for psychiatry and various movement disorders. This approach identifies the kind of pathophysiology that underwrites psychopathology—and points to certain psychotherapeutic and psychopharmacological targets, which may stand in mechanistic relation to each other. HIGHLIGHTS: The 'mind' emerges from Bayesian belief updating in the 'brain' Psychopathology can be read as aberrant belief updating. Aberrant belief updating follows from any neuromodulatory synaptopathy